OK4U: E-Government Through The Eyes of The Abandoned Group in Malaysia / Alif Haikal Saiful and Rabiatul Adawiyah Mohamad Akbal - Saiful, Alif Haikal; Mohamad Akbal, Rabiatul Adawiyah (2021)
While the majority of the people believe in the notion of 'The world is at the end of your fingertips, it is an absolute lie towards the minority group of People with Disability (PWD) when deliberately excluding them in service recipients in e-government services. As of January 2021, there were an estimated 592,856 (Jabatan Kebajikan Masyarakat, 2021) registered as Malaysia's PWD. While constantly being denied in the physical world, they are also facing discrimination in the cyber world as the majority of existing Malaysian government portals still do not consider the values of accessibility thus ignoring and delaying them in receiving services. According to the United Nations E-Government Development Database (UNeGovDD), Malaysia ranks at 47 out of 193 countries on the E-government development index in 2020. Hence, a universal and inclusive web design is needed to improve e- government's performance that caters to regular consumers while considering the PWDs users too. OK4U is an initiative to opt for a widget extension tool that can destroy the inaccessibility barriers designed for PWD via various features, hence complementing their needs when browsing e-government government portals. The purpose is to create and improve users' experience for PWD when surfing the government's portals. The policymakers should also urge all the service providers to provide an OKU- friendly web while all the features should also apply to all devices be it through personal computers or smartphones while being in a standardized design. Through its implementation in every government's portal with a consistent and standardised design, it can be an impetus for bigger national development projects and websites which are accessible and inclusive. Given the continuous awareness of the community needs to be nurtured, in a time when the spirit of goodwill of the country will be further enhanced, thereby ensuring the well-being of the people.